Effect of Immobilization Methods on the Production of Polyethylene-cellulose Biocomposites via Ethylene Polymerization with Metallocene/MAO Catalyst - Praonapa Tumawong; Ekrachan Chaichana; Bunjerd Jongsomjit (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
Polyethylene-cellulose biocomposites were synthesized here via the ethylene polymerization with metallocene as a catalyst along with methylaluminoxane (MAO) as a cocatalyst. The immobilization method in which the catalyst or cocatalyst is fixed onto the catalytic filler (cellulose) can be classified into 3 methods according to the active components fixed onto the filler surface: 1) only metallocene catalyst (Cellulose/Zr), 2) only MAO cocatalyst (Cellulose/MAO) and 3) mixture of metallocene and MAO (Cellulose/(Zr+MAO)). It was found that the different immobilization methods or different fillers altered the properties of the obtained composites and also the catalytic activity of the polymerization systems. It was found that Cellulose/MAO provided the highest catalytic activity among all fillers due to a crown-alumoxane complex, which caused the heterogeneous system with this filler behaved similarly to the homogeneous system. The different fillers also produced the biocomposites with some different properties such as crystallinity which Cellulose/Zr provided the highest crystallinity compared with other fillers as observed by a thermal gravimetric analysis-differential scanning calorimetry (TGA-DSC). Nevertheless, the main crystal structure indicated to the typical polyethylene was still observed for all obtained biocomposites with different fillers as observed by an X-ray diffractometer (XRD). Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).